Mold and method for testing external quantum efficiency of perovskite module subcells
Patent Information
- Application Number
- CN202510444540.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2026-10-20
AI Technical Summary
[0008]首先是边缘效应差异,模组中相邻子电池的激光刻蚀区域会形成微米级的性能过渡带,这种边缘复合效应在小面积器件中难以复现;
[0043](1)本发明通过设计用于测试钙钛矿模组中子电池的外量子效率的模具,可在钙钛矿子电池形成的串联电路中测试待测子电池的外量子效率,有利于对钙钛矿模组电池性能的整体认识,从而有利于优化钙钛矿模组电池;
Smart Images

Figure HDA0005352144680000011 
Figure HDA0005352144680000012 
Figure HDA0005352144680000021
Abstract
Description
Technical Field
[0001] This invention relates to the field of perovskite solar cell technology, and more specifically to a mold and method for testing the external quantum efficiency of neutron cells in perovskite modules. Background Technology
[0002] Perovskite solar cells exhibit excellent photoelectric conversion efficiency; the photoelectric conversion efficiency of small-area perovskite solar cells has exceeded 26%, comparable to commercially available crystalline silicon cells. However, when device sizes increase from the laboratory-level 0.1 cm... 2 When scaling up to the 100-square-centimeter scale required for industrialization, the photoelectric conversion efficiency of perovskite solar cells drops precipitously, becoming a key bottleneck restricting industrialization. Data shows that currently, the 30cm... 2 Certified photoelectric conversion efficiencies for large-area perovskite modules are generally below 20%, representing a gap of over 6 percentage points compared to the record photoelectric conversion efficiencies of small-area cells. Narrowing the efficiency gap between perovskite modules and small-area perovskite solar cells is crucial for industrialization.
[0003] Currently, laser scribing technology is mainly used to divide large-area perovskite solar cells into multiple perovskite sub-cells, which are then connected in series to form perovskite modules. This improves the overall voltage and fill factor of the device, thereby enhancing the efficiency of perovskite solar cells.
[0004] External quantum efficiency (EQE) is one of the main performance indicators of optoelectronic devices. Its value is the ratio of the number of collected electrons to the number of incident photons.
[0005] Since a perovskite module is formed by connecting multiple perovskite sub-cells in series, the overall external quantum efficiency (OQE) of the perovskite module depends on each individual perovskite sub-cell, and the OQE of each individual perovskite sub-cell is also affected by the OQEs of other sub-cells in the module. Therefore, testing the OQE of each perovskite sub-cell in a perovskite module is of great significance for analyzing perovskite solar cells. For example, large-area perovskite modules will degrade after long-term operation; by analyzing the changes in the OQE of each perovskite sub-cell, the degradation mechanism can be analyzed, thereby improving operational stability.
[0006] However, current testing of the external quantum efficiency of perovskite solar cells mainly involves using a large-area light source applied to the perovskite module for overall external quantum efficiency testing. On the one hand, this has the problems of poor wavelength accuracy, intensity, stability and uniformity of large-area light sources, as well as high cost. On the other hand, it cannot obtain the external quantum efficiency of each perovskite sub-cell in the perovskite module.
[0007] To test the external quantum efficiency of perovskite sub-cells within perovskite modules, some reports have described fabricating small-area cells with structures similar to those in perovskite modules and then testing the external quantum efficiency of these small-area cells independently. However, this method overlooks three key differences between the small-area cells and the perovskite sub-cells located within the perovskite module:
[0008] First, there is the difference in edge effects. The laser-etched areas of adjacent sub-cells in the module will form a micron-level performance transition band. This edge recombination effect is difficult to reproduce in small-area devices.
[0009] Secondly, there is the difference in stress distribution. The residual stress in the thin film caused by the large-area coating process in the module will significantly change the carrier transport characteristics at the perovskite grain boundaries.
[0010] Furthermore, there are differences in process uniformity. The fabrication processes of small-area battery devices prepared by spin coating are different from those of perovskite modules, resulting in significant differences in process uniformity between small-area batteries and perovskite modules, thus leading to performance differences.
[0011] Therefore, this method, which uses the external quantum efficiency of the small-area cell as the external quantum efficiency of the perovskite module neutron cell, may mislead researchers' understanding of the performance of perovskite module cells and hinder the process optimization of perovskite module neutron cells. Summary of the Invention
[0012] In view of the above-mentioned technical status, the present invention provides a mold for testing the external quantum efficiency of sub-cells in perovskite modules. The mold can be used to directly test the external quantum efficiency of perovskite sub-cells in perovskite modules, and the mold can be adjusted according to the shape and size of perovskite sub-cells, thus having good applicability.
[0013] The technical solution provided by this invention is: a mold for testing the external quantum efficiency of a perovskite module sub-cell, wherein the perovskite module includes a plurality of perovskite sub-cells, and each perovskite sub-cell is connected in series to form a series circuit.
[0014] The mold consists of three parts;
[0015] The first part has a groove structure with an opening at the bottom;
[0016] The second part has a columnar structure, and through holes are provided inside the columnar structure along the height direction of the columnar structure; along the height direction of the columnar structure, the surface of one end of the columnar structure is called the upper surface, and the surface of the other end is called the lower surface;
[0017] The third part is used to cover the upper surface of the perovskite sub-cell, and the third part is provided with perforations;
[0018] The upper surface of the columnar structure is sealed to the bottom of the groove (i.e., the connection is a sealed structure), and the lower surface is sealed to the third part; one end of the through hole is connected to the bottom opening of the groove, and the other end is connected to the perforation;
[0019] The diameter of the perforation is less than or equal to the diameter of the opening at the bottom of the groove, the diameter of one end of the through hole, and the diameter of the other end of the through hole.
[0020] In the first part, at least the outer wall of the groove structure is made of a light-shielding material to prevent external light from entering the groove structure.
[0021] In the second part, at least the outer wall of the columnar structure is made of a light-shielding material to prevent external light from entering the columnar structure;
[0022] The portion of the third part used to cover the upper surface of the perovskite sub-cell is made of a light-shielding material so that external light cannot reach the upper surface of the perovskite sub-cell.
[0023] The structure of the third part is not limited; it can be in the form of a flat plate or an open umbrella shape, etc.
[0024] Preferably, the height of the second part (i.e., along the height of the columnar structure) is adjustable.
[0025] Preferably, in order to improve the irradiation rate of the light beam in the perovskite sub-cell and avoid the light beam being blocked, the diameter of the bottom opening of the tank is less than or equal to the diameter of one end of the through hole and less than or equal to the diameter of the other end of the through hole, so that the light beam passing through the bottom opening of the tank can pass through the through hole.
[0026] In one implementation, the perforation can be nested at the other end of the through hole, and the diameter of the perforation can be adjusted according to the light area illuminating the surface of the sub-cell under test.
[0027] As one implementation method, the first part is made of light-shielding stainless steel.
[0028] As one implementation method, the second part is made of light-shielding stainless steel.
[0029] As one implementation method, the material of the third part is light-shielding stainless steel.
[0030] As one implementation method, a transparent front electrode is provided on the upper surface of each perovskite sub-cell, and a back electrode is provided on the lower surface. The perovskite sub-cells are connected in series by connecting the front electrode and the back electrode of each perovskite sub-cell.
[0031] The structure of the perovskite sub-cell is not limited. As one implementation, the perovskite sub-cell has a stacked structure, which includes, in sequence, an electron transport layer, a first interface modification layer, a perovskite layer, a second interface modification layer, a hole transport layer, and an interface protection layer.
[0032] To further improve the light-shielding effect of the mold, preferably, the inner wall of at least the groove structure in the first part and / or the inner wall of at least the columnar structure in the second part are coated with black paint to avoid the refraction and reflection of light beams, thereby improving the test accuracy.
[0033] The present invention also provides a method for testing the external quantum efficiency of a perovskite module neutron cell using the aforementioned mold, as detailed below:
[0034] The mold is set at the location of the sub-battery to be tested, so that the third part covers the upper surface of the sub-battery to be tested;
[0035] A first light source is used to emit a first beam of light to illuminate the sub-battery under test. The first beam of light enters the through hole through the bottom opening of the groove, and then illuminates the upper surface of the sub-battery under test through the perforation.
[0036] A second light source is used, which generates a second beam to illuminate the remaining perovskite sub-cells in the perovskite module, excluding the sub-cell under test; the light intensity of the second light source is greater than the light intensity of the first light source.
[0037] The current of the series circuit is tested, which is the current of the sub-cell under test. The external quantum efficiency of the sub-cell under test is obtained by measuring the current of the sub-cell under test and the intensity of the first light source.
[0038] The first light source is not limited, but preferably, the first light source is variable wavelength monochromatic light.
[0039] The second light source is not limited, but considering cost, white light is preferred.
[0040] Preferably, the light intensity of the first light source is 10 μW / cm². 2 -1000μW / cm 2 .
[0041] Preferably, the light intensity of the second light source is 1 W / cm². 2 -200W / cm 2 .
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) This invention designs a mold for testing the external quantum efficiency of sub-cells in a perovskite module. The external quantum efficiency of the sub-cells under test can be tested in a series circuit formed by perovskite sub-cells. This is beneficial for the overall understanding of the performance of perovskite module batteries, and thus beneficial for optimizing perovskite module batteries.
[0044] (2) In the mold of the present invention, the height of the second part is preferably adjustable so that perovskite modules of different thicknesses can be tested for external quantum efficiency at the standard height. The shape and area of the third part can be adjusted according to the shape and area of the upper surface of the perovskite sub-cell under test. Therefore, the mold is suitable for measuring perovskite sub-cells of various thicknesses and areas and has good versatility. In addition, by adjusting the diameter of the perforation in the third part, the illumination area on the sub-cell under test can be adjusted, which improves the controllability of external quantum efficiency measurement.
[0045] (3) The present invention sets the mold at the position of the sub-battery to be tested, uses low-intensity light to irradiate the sub-battery to be tested, uses high-intensity light to irradiate the other sub-batteries in the module, and uses the mold to prevent high-intensity light from irradiating the sub-battery to be tested, so that the sub-battery to be tested becomes a sub-battery that limits the current of the series circuit, thereby realizing the measurement of the external quantum efficiency of the sub-battery to be tested in the module, and has testing accuracy. Attached Figure Description
[0046] Figure 1 This is a schematic diagram of the structure of the mold used to test the external quantum efficiency of the perovskite module neutron cell in Embodiment 1 of the present invention.
[0047] Figure 2 yes Figure 1 A schematic diagram of its breakdown.
[0048] Figure 3 It is the light beam that passes through Figure 1 The diagram shows the mold irradiating the perovskite sub-cell under test.
[0049] Figure 4 It is to utilize Figure 1 A schematic diagram of the external quantum efficiency of the sub-cell under test in the perovskite module for testing the mold.
[0050] Figure 1-4 The accompanying figure labels are as follows:
[0051] Part 10, bottom opening of the tank 11;
[0052] Part 20, through hole 21, one end of through hole 22, the other end of through hole 23;
[0053] Part 30, Perforation 31;
[0054] Perovskite subcell 40; first beam 50; second beam 60. Detailed Implementation
[0055] The present invention will be further described in detail below with reference to the embodiments. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention. Non-essential improvements and adjustments made to the present invention by those skilled in the art based on the above description of the present invention are still within the protection scope of the present invention.
[0056] In this invention, the terms "including" and "comprising" should be interpreted as including rather than exclusive or exhaustive; that is, "including but not limited to".
[0057] like Figure 1-2 As shown, the mold used to test the external quantum efficiency of the perovskite module neutron cell consists of three parts:
[0058] The first part 10 has a groove structure with an opening at the bottom of the groove, referred to as the bottom opening 11 of the groove;
[0059] The second part 20 has a columnar structure. Inside the columnar structure, through holes 21 are provided along the height direction of the columnar structure. One end of the through hole is called the through hole end 22, and the other end of the through hole is called the through hole end 23. Along the height direction of the columnar structure, the surface of one end of the columnar structure is called the upper surface, and the surface of the other end is called the lower surface.
[0060] The third part 30 is used to cover the upper surface of the perovskite sub-cell 40, and the third part 30 is provided with a perforation 31.
[0061] The upper surface of the columnar structure of the second part 20 is sealed to the bottom of the first part of the tank (i.e., the connection is a sealed structure), and the lower surface of the columnar structure is sealed to the third part 30. One end 22 of the through hole connects to the bottom opening 11 of the tank, and the other end 23 of the through hole connects to the through hole 31.
[0062] The diameter of the perforation 31 is less than or equal to the diameter of the bottom opening 11 of the groove, the diameter of one end 22 of the through hole, and the diameter of the other end 23 of the through hole, so that the diameter of the beam passing through the bottom opening 11 of the groove and the through hole 21 can be adjusted.
[0063] In the first part 10, at least the outer wall of the groove structure is made of a light-shielding material to prevent external light from entering the groove structure. In the second part 20, at least the outer wall of the columnar structure is made of a light-shielding material to prevent external light from entering the columnar structure. In the third part 30, at least the portion used to cover the upper surface of the perovskite sub-cell 40 is made of a light-shielding material to prevent external light from illuminating the upper surface of the perovskite sub-cell 40.
[0064] In this embodiment, the first part 10 is made of light-shielding stainless steel, the second part 20 is made of light-shielding stainless steel, and the third part 30 is made of light-shielding stainless steel. Furthermore, in this embodiment, the inner walls of at least the grooved structure in the first part 10, and / or the inner walls of at least the columnar structure in the second part 20, are coated with black paint to avoid refraction and reflection of the light beam, thereby improving test accuracy.
[0065] In this embodiment, in order to improve the irradiation rate of the light beam in the perovskite sub-cell 40 and avoid the light beam being blocked, the diameter of the bottom opening 11 of the tank is less than or equal to the diameter of one end 22 of the through hole, and less than or equal to the diameter of the other end 23 of the through hole.
[0066] In this embodiment, the structure of the third part is not limited; it can be in the form of a flat plate or an unfolded umbrella shape, etc.
[0067] In this embodiment, the height of the second part 20 is adjustable, so that perovskite modules of different thicknesses can be tested for external quantum efficiency at a standard height.
[0068] In this embodiment, the shape and area of the third part 30 can be adjusted according to the shape and area of the upper surface of the perovskite sub-cell 40 to be tested. Therefore, the mold is suitable for measuring perovskite sub-cells of various thicknesses and areas.
[0069] In this embodiment, as Figure 4 As shown, a transparent front electrode is provided on the upper surface of each perovskite sub-cell, and a back electrode is provided on the lower surface. When a certain perovskite sub-cell is the sub-cell under test, the third part 30 is used to cover the front electrode of the sub-cell under test.
[0070] In this embodiment, as Figure 4 As shown, the perovskite module comprises several perovskite sub-cells, which are connected in series to form a series circuit. The two ends of the circuit are electrode output terminals. The specific method for detecting the external quantum efficiency of the sub-cells in the perovskite module using this model is as follows:
[0071] The mold is set at the location of the sub-cell under test, so that the third part 30 covers the front electrode of the sub-cell under test.
[0072] The test cell is illuminated by a first light source. In this embodiment, the first light source is a variable wavelength monochromatic light source with an intensity of 50 μW / cm². 2 The monochromatic light beam emitted by the monochromatic light source enters the through hole 21 through the opening 11 at the bottom of the tank, and then illuminates the sub-cell under test through the perforation 31.
[0073] The perovskite sub-cells in the perovskite module, excluding the sub-cell under test, are illuminated using a second light source. The light intensity of the second light source is greater than that of the first light source. In this embodiment, the second light source is a white polarized LED with an intensity of 150 W / cm². 2 Because of the obstruction of the mold, the white polarized light from the LED cannot enter the mold and therefore cannot illuminate the battery under test.
[0074] The current in the series circuit is tested; this current is the current of the sub-cell under test. The external quantum efficiency of the sub-cell under test is obtained by measuring the current of the sub-cell under test and the light intensity illuminating it. The illumination area on the sub-cell under test can be controlled by adjusting the perforation diameter.
[0075] The above embodiments provide a detailed description of the technical solution of the present invention. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A mold for testing the external quantum efficiency of a sub-cell in a perovskite module, wherein the perovskite module comprises a plurality of perovskite sub-cells connected in series to form a series circuit. Its characteristics are: The mold consists of three parts; The first part has a groove structure with an opening at the bottom; The second part has a columnar structure, and through holes are provided inside the columnar structure along its height. Along the height direction of the columnar structure, the surface at one end of the columnar structure is called the upper surface, and the surface at the other end is called the lower surface. The third part is used to cover the upper surface of the perovskite sub-cell, and the third part is provided with perforations; The upper surface of the columnar structure is sealed to the bottom of the groove, and the lower surface is sealed to the third part; one end of the through hole is connected to the opening at the bottom of the groove, and the other end is connected to the perforation; The diameter of the perforation is less than or equal to the diameter of the bottom opening of the groove, the diameter of one end of the through hole, and the diameter of the other end of the through hole. In the first part, at least the outer wall of the groove structure is made of light-shielding material; in the second part, at least the outer wall of the columnar structure is made of light-shielding material; and in the third part, at least the portion used to cover the upper surface of the perovskite sub-cell is made of light-shielding material.
2. The mold as described in claim 1, characterized in that: The third part is either flat or unfolded like an umbrella.
3. The mold as described in claim 1, characterized in that: The height of the second part is adjustable.
4. The mold as described in claim 1, characterized in that: The diameter of the bottom opening of the groove is less than or equal to the diameter of one end of the through hole, and less than or equal to the diameter of the other end of the through hole.
5. The mold as described in claim 1, characterized in that: Each perovskite sub-cell has a transparent front electrode on its upper surface and a back electrode on its lower surface. The perovskite sub-cells are connected in series by connecting the front and back electrodes of each sub-cell.
6. The mold as described in claim 1, characterized in that: The illumination area on the sub-cell under test can be adjusted by adjusting the diameter of the perforation in the third part.
7. The mold as described in claim 1, characterized in that: One or more of the materials in the first part, the second part, and the third part are selected from light-shielding stainless steel.
8. The mold as described in claim 1, characterized in that: The inner wall of at least the groove structure in the first part, and / or the inner wall of at least the columnar structure in the second part, is coated with black paint.
9. A method for testing the external quantum efficiency of a perovskite module neutron cell using the mold described in any one of claims 1 to 8, characterized in that: The mold is set at the location of the sub-battery to be tested, so that the third part covers the upper surface of the sub-battery to be tested; A first light source is used to emit a first beam of light to illuminate the sub-battery under test. The first beam of light enters the through hole through the bottom opening of the groove, and then illuminates the upper surface of the sub-battery under test through the perforation. A second light source is used, which generates a second beam to illuminate the remaining perovskite sub-cells in the perovskite module, excluding the sub-cell under test; the light intensity of the second light source is greater than the light intensity of the first light source. The current of the series circuit is tested, which is the current of the sub-cell under test. The external quantum efficiency of the sub-cell under test is obtained by comparing the current of the sub-cell under test with the intensity of the first light source.
10. The method of claim 9, characterized in that: The first light source is variable wavelength monochromatic light.
11. The method of claim 9, characterized in that: The second light source is white light.
12. The method of claim 9, characterized in that: The light intensity of the first light source is 10 μW / cm 2 -1000μW / cm 2 The light intensity of the second light source is 1 W / cm². 2 -200W / cm 2 .